Scaling Test Automation in CI/CD Pipelines Using Docker and Kubernetes - Praveen Kumar Koppanati (North American Journal of Engineering Research, 2024)
Continuous Integration and Continuous Delivery (CI/CD) have become critical for modern software development lifecycles, emphasizing the need for automated testing to ensure application quality, stability, and security. The increasing complexity of microservices architectures and fast release cycles have necessitated scalable solutions for test automation. Docker and Kubernetes have emerged as essential technologies for containerizing and orchestrating testing environments, enabling development teams to scale their testing efforts seamlessly. This paper examines the best practices and methodologies for integrating Docker and Kubernetes into CI/CD pipelines to scale test automation. We explore the architectural benefits, performance considerations, challenges, and tools that facilitate the implementation of scalable test automation frameworks. We also provide case studies to demonstrate the successful adoption of these technologies in industry. Finally, we discuss future trends and innovations that could further enhance test automation scalability